A QGIS plugin to tailor SWAT watershed delineations to lake and reservoir waterbodies. (October 2018) - Molina-Navarro, Eugenio; Nielsen, Anders; Trolle, Dennis
Abstract: Coupling watershed and lake models is a powerful approach for providing lake or reservoir inputs and for simulating how land use scenarios may impact lake ecosystems. SWAT (Soil and Water Assessment Tool) is one of the most widely used watershed models for this purpose. However, as outlets for watershed delineation in SWAT should be in the river network, modellers may – when modelling the inputs to a waterbody boundary – make choices leading to imprecise results. The impact of these choices on the accuracy of a coupled model can be highly relevant as they have a direct effect on the size of the delineated watershed. In this paper, we describe the design and development of SWAT2lake, a tool that remedies such imprecise delineation of watersheds to lakes and reservoirs. SWAT2lake has been designed as a plugin for the QGIS software that works in parallel with QSWAT and it is available through wet.au.dk. Graphical abstract: Image Highlights: We present SWAT2lake, a tool to tailor the watershed of a waterbody to its outline. SWAT2lake has been designed as a plugin for QGIS that works in parallel with QSWAT. A practical application for the Danish Lake Arreskov watershed is presented. SWAT2lake is open source software, and it is available through wet.au.dk.